Kajian Visual Urban Signage pada Koridor Jalan Utama BSD Boulevard Utara - Anggun Nur Apipah (Universitas Medan Area, 2026)
Urban Signage plays an important role in shaping the visual character of an area and providing information and direction for users of urban space. This study aims to identify urban Signage elements on the main road corridor of BSD Boulevard Utara, this research area is also a rapidly developing modern area in South Tangerang. This study was conducted to evaluate the visual quality, readability, placement, and suitability of Signage with the function of the area and the principles of sustainable urban design. This study uses a qualitative descriptive method with data collection techniques carried out through observation, visual documentation, and mapping of Signage locations. The analysis was carried out by categorizing the type of Signage and assessing visual aspects such as size, color, typography, and integration with other urban elements. The results of this study are expected to show whether the placement of Signage is in accordance with standards, especially commercial Signage that dominates the area. This study can also be a recommendation as a guideline for urban Signage design that considers the character of the area, Signage function, and user comfort.